Sofosbuvir/Velpatasvir/Voxilaprevir for patients with HCV who previously received a Sofosbuvir/Velpatasvir‐containing regimen: Results from a retreatment study. Issue 6 (27th February 2019) - Ruane, Peter; Strasser, Simone I.; Gane, Edward J.; Hyland, Robert H.; Shao, Jiang; Dvory‐Sobol, Hadas; Tran, Tram; Stamm, Luisa M.; Brainard, Diana M.; Nyberg, Lisa; Shafran, Stephen
Summary: This study evaluated 12‐week retreatment with sofosbuvir/velpatasvir/voxilaprevir in patients with chronic hepatitis C virus (HCV) infection who did not achieve sustained virologic response after previous treatment with a sofosbuvir‐ and velpatasvir‐containing regimen. All 31 patients maintained a sustained virologic response 12 weeks after the last sofosbuvir/velpatasvir/voxilaprevir dose.